A Multimodal Analysis of English Textbook for Vocational High School: A Study of English For Specific Purposes - Hamidah, Mimi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
As part of English for specific purposes, English books for vocational high schools in Indonesia have been widely studied. Many previous researchers have studied need analysis in English books for Vocational High Schools, while studies related to a multimodal approach are still lacking. Therefore, a study of visual and verbal components in the textbook is conducted in this research. The data is taken from multimodal teaching materials in the English book